2020
DOI: 10.3389/fneur.2020.579070
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and Novel Coronavirus Infection in Humans: A Systematic Review and Meta-Analysis

Abstract: Background: As the world witnessed the devastation caused by the coronavirus disease 2019 (COVID-19) outbreak, a growing body of literature on COVID-19 is also becoming increasingly available. Stroke has increasingly been reported as a complication of COVID-19 infection. However, a systematic synthesis of the available data has not been conducted. Therefore, we performed a systematic review and meta-analysis of currently available epidemiological, clinical, and laboratory data related to both stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 86 publications
1
38
0
1
Order By: Relevance
“…In a meta-analysis of 28 articles related to stroke and COVID-19, the average number of days to develop stroke among patients after the onset of COVID-19 infection was 6.9 ± 4.5 days. (6) Some series, similar to our data, have reported that patients may present with stroke with simultaneous asymptomatic COVID-19 infection. (11,17) In concordance with stroke data in non-COVID-19 times, and with data published on stroke in COVID-19, the vast majority of our CVAs were infarcts.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a meta-analysis of 28 articles related to stroke and COVID-19, the average number of days to develop stroke among patients after the onset of COVID-19 infection was 6.9 ± 4.5 days. (6) Some series, similar to our data, have reported that patients may present with stroke with simultaneous asymptomatic COVID-19 infection. (11,17) In concordance with stroke data in non-COVID-19 times, and with data published on stroke in COVID-19, the vast majority of our CVAs were infarcts.…”
Section: Discussionsupporting
confidence: 86%
“…(15) A pooled frequency of seven studies using the fixed effect model, estimated the incidence of acute stroke in COVID-19 to be 1.1%. (6) The proposed mechanisms include a virus induced prothrombotic state, endothelial injury, vasculitis, cardiomyopathy, microvascular thrombosis and cytokine storm. (79) We report our experience of COVID-19 with stroke over a period of eight months spanning March to October 2020.…”
Section: Introductionmentioning
confidence: 99%
“…This result is lower than a previously reported incidence (0.7%; 95% CI 0.50%–0.9%) 51 . The incidence of hemorrhagic stroke among all stroke types in COVID-19 patients fluctuated, with 12.2% in May 2020 52 , 9.7% in June 2020 53 , 17.2% in July 2020 54 , 11.6% in September 2020 55 , and 28.42% in the present systematic review.…”
Section: Discussionmentioning
confidence: 56%
“…The cause of ischemic stroke is multifactorial in those with SARS-CoV-2 infection, and it may be due to systemic embolization and diffuse microvascular thrombosis (attributed to a significant increase in prothrombotic factors) 53 . In our systematic review, the mortality rate of COVID-19 patients who experienced ischemic stroke was 36.23%.…”
Section: Discussionmentioning
confidence: 99%
“…A wide sample of neurological symptoms and SARS-CoV2 infection-associated diseases have already been described—large vessel strokes being one of the most life-threatening events related to COVID-19 ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%